SOFT TENNIS AND VOLLEYBALL CONTEXTS IN ASIAN GAMES FOR PISA-LIKE MATHEMATICS PROBLEMS - Jannah, Riya Dhotul; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi (Journal on Mathematics Education, 2019)
This study aims to produce valid and practical PISA-like mathematics problems of uncertainty and data content by using soft tennis and volleyball contexts in Asian Games. It also aims to find out the potential effect of the problems on students' mathematical literacy. The method used in this study was design research with the type of development studies. The validity was viewed from expert assessment regarding the content, constructs, language, and students’ comments to the clarity of the problems in the one-to-one phase. Then, the practicality was viewed in the small group phase, and it was found that the students could understand the problem well. Based on the answers from 33 tenth-grade students of senior high school, it was found that the problems had potential effects that arouse the ability to use symbolic, formal, and technical language, as well as the ability of operation, communication, and representation. With the problem of the soft tennis context, five students could apply the ability to use symbolic, formal, and technical language, and operations, 12 students could apply representation ability, and 16 students could apply the communication ability. Meanwhile, with the problem of the volleyball context, 18 students could apply the communication ability, and nine students could apply the representation ability.